Violent activity detection through surveillance camera using deep learning - Miah, Parvez; Haque, Abrar Ahbabul; Imran, Abdullah Al; Hassan, MD. Radip; Rahman, Rafiur (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.